Nutritional and Functional New Perspectives and Potential Health Benefits of Quinoa and Chia Seeds - Aparna Agarwal; Rizwana; Abhishek Dutt Tripathi; Tarika Kumar; Kanti Prakash Sharma; Sanjay Kumar Singh Patel (MDPI AG, 2023)
Quinoa (Chenopodium quinoa Willd) and chia (Salvia hispanica) are essential traditional crops with excellent nutritional properties. Quinoa is known for its high and good quality protein content and nine essential amino acids vital for an individual's development and growth, whereas chia seeds contain high dietary fiber content, calories, lipids, minerals (calcium, magnesium, iron, phosphorus, and zinc), and vitamins (A and B complex). Chia seeds are also known for their presence of a high amount of omega-3 fatty acids. Both quinoa and chia seeds are gluten-free and provide medicinal properties due to bioactive compounds, which help combat various chronic diseases such as diabetes, obesity, cardiovascular diseases, and metabolic diseases such as cancer. Quinoa seeds possess phenolic compounds, particularly kaempferol, which can help prevent cancer. Many food products can be developed by fortifying quinoa and chia seeds in different concentrations to enhance their nutritional profile, such as extruded snacks, meat products, etc. Furthermore, it highlights the value-added products that can be developed by including quinoa and chia seeds, alone and in combination. This review focused on the recent development in quinoa and chia seeds nutritional, bioactive properties, and processing for potential human health and therapeutic applications.